The Effect of Concentration of Household Waste Liquid Organic Fertilizer and Planting Media on Growth and Production of Cayenne Pepper (Capsicum frutescens L: Efek Konsentrasi Pupuk Organik Cair Limbah Rumah Tangga dan Media Tanam Terhadap Pertumbuhan dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L)” - Mahdalena; Anis Munandar (Agrifarm : Jurnal Ilmu Pertanian, 2021)
Effect of Concentration of Household Waste Liquid Organic Fertilizer and Planting Media on Growth and Production of Cayenne Pepper (Capsicum frutescens L)". The purpose of the study was to determine the effect of liquid organic fertilizer from rice washing waste on various growing media and the interaction of the two treatments on the growth and production of cayenne pepper (Capsicum frutescens L). This research was carried out for 4 months, starting from December 2020 to March 2021, the location of the research on the Practicum Field of the Faculty of Agriculture, University of Widya Gama Mahakam Samarinda is located on Jln. K. H Wahid Hasyim, Sempaja Village, North Samarinda District, Samarinda City, East Kalimantan Province. The research method used a randomized block design with a 4 x 4 factorial experiment consisting of 3 replications. The first factor is organic fertilizer of rice washing waste (P) which consists of 4 levels, namely: P0 (control), P1 250 ml + 750 ml water, P2 500 ml + 500 ml water, and P3 750 ml + 250 ml water. The second factor is the planting medium (M) which consists of 4 levels, namely M0 (control) 15 kg, M1 soil 10 kg + husk charcoal 5 kg (2: 1), M2 soil 10 kg + sawdust 5 kg (2: 1) , M3 soil 5 kg + husk charcoal 5 kg + sawdust 5 kg ( 1 : 1 : 1 ). Observation variables were plant height, stem diameter, harvest age, and fruit weight. The results showed that the effect of liquid organic fertilizer from rice washing waste on various planting media and the interaction of the two treatments did not give the best effect on the growth and production of cayenne pepper (Capsicum frutescens L).